Determinação de cobre em vinhos usando extração em fase sólida magnética, pontos quânticos de carbono e espectrofluorimetria - Costa, Matheus de Holanda (2018)
The wine establishes standards of identity and quality, thus physical-chemical analyzes are realized to verify its nutritional value and control the quality of the product. Between the parameters to be monitored we can mention the content of 9 metallic ions in wine. High concentrations of these ions can affect organoleptic characteristics such as aroma, taste and color, forming precipitates or turbidity, as well as an excessive intake causes a possible intoxication. One of the metals to be 9controlled is copper, high concentrations of it promote turbidity and sedimentation, as well as deterioration of flavor, which is a physiological characteristic associated with taste and smell. For the determination of metals content in wine the atomic absorption spectrometry is the technique recommended by the OIV. As the wine is a complex matrix, sample preparation techniques are necessary before making the measurement. The wet digestion method is the most used as sample (wine) pretreatment, being that it needs a high time of preparation and use of chemical solvents. In order to optimize the sample preparation for determination of metal ions, two nanoparticles were used: (1) extraction in magnetic solid phase, where the analyte is adsorbed using magnetic nanoparticles33 of magnetite (Fe3O4) coated with alumina (Al2O3) and functionalized with sodium dodecyl sulfate and 1- (2-pyridylazo) 2-naphthol; (2) elution and detection of the analyte by quantum carbon dots (QCDs) from a bioprecursor of pineapple for the fluorescent determination of ion copper (II). The performance of the proposed method was evaluated by the determination of copper (II) in samples of wine, the paired t-test (in triplicate) indicated that there is no significant differences between the results at a confidence level of 95%. The methodology used allowed to estimate limits of detection and the limit of quantification of 8.20 and 27.34 µg.L-1, respectively. The study of metal ion interferers was carried out successfully, revealing no significant percentage interference (= 5 %). The proposed method obtained satisfactory results compared to the reference method.